The Moderating Role of Autonomy Support Profiles in the Association Between Grit and Externalizing Problem Behavior Among Family-Bereaved Adolescents - Feng, Lijuan; Lan, Xiaoyu (Frontiers in Psychology, 2020)
Research has consistently documented that the death of a close family member can disrupt a family’s functional equilibrium and has a deleterious effect on adolescents’ adaption, little attention, however, has been paid to behavioral adaption of adolescents following a loss in a collective setting. Attempting to fill this research gap, the objectives of the current study are: (1) to identify autonomy support profiles based on two centered figures (parents and head teachers), and (2) to examine whether these emerging profiles may moderate the association between the two dimensions of grit (perseverance and consistency) and externalizing problem behavior in Chinese family-bereaved adolescents. A total of 763 family-bereaved adolescents aged from 13 to 18 years (60.3% girls; M age = 15.74; SD = 1.53) were involved in the current study; they were asked to fill a battery of self-report questionnaires. A latent profile analysis revealed three autonomy support profiles: HPHT (n = 598, high parental autonomy support-high teacher autonomy support), HPLT (n = 34, high parental autonomy support-low teacher autonomy support), and LPLT (n = 131, low parental autonomy support-low teacher autonomy support). Moreover, results from linear regression analyses, after controlling for relevant bereavement variables, sociodemographics, and social desirability, showed that perseverance and consistency were negatively related to externalizing problem behavior for adolescents within the HPHL profile; nevertheless, the association between perseverance and externalizing problem behavior turned to be positive for adolescents within the HPLT profile. The current study sheds light on the variability of the association between grit and family-bereaved adolescents’ behavioral adaption, and further enriches the beneficial effect of autonomy support on adaptive functions in a collective cultural setting. The interplay between grit and autonomy support from parents and teachers has a significant influence on buffering externalizing problem behavior among family-bereaved adolescents.